2024
DOI: 10.1109/access.2024.3380372
|View full text |Cite
|
Sign up to set email alerts
|

Radio Frequency Energy Harvesting for Underground Sensor Nodes: Possibilities and Challenges

Emmanuel Mahenge,
Ramadhani Sinde,
Mussa Ally Dida
et al.

Abstract: Radio frequency energy harvesting (RFEH) is considered an optimal and environmentally friendly solution for energizing sensor devices and prolonging the lifetime of wireless sensor networks (WSNs). Despite being studied and experimented in several environments where WSNs are used, studies and experiments related to RFEH in underground wireless systems are limited to near-field wireless power transfer (WPT), measurement of received signal strength, and current conduction. The goal of this study is to examine th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 109 publications
0
1
0
Order By: Relevance
“…This research revealed that factors like burial depth, antenna type, transmission power, receiver height above the ground, and soil type have significant impacts on signal transmission. They deployed the system that could receive signal BG2BG only in the range of 4 to 20 m. In addition, low-frequency RF and EM signals require large antennae to generate and detect signals [25], which is logistically challenging to install in soil environments. Additionally, soil permittivity varies with the change in moisture content.…”
Section: Modern Wusn Technologies and Advancement Of Acousticsmentioning
confidence: 99%
“…This research revealed that factors like burial depth, antenna type, transmission power, receiver height above the ground, and soil type have significant impacts on signal transmission. They deployed the system that could receive signal BG2BG only in the range of 4 to 20 m. In addition, low-frequency RF and EM signals require large antennae to generate and detect signals [25], which is logistically challenging to install in soil environments. Additionally, soil permittivity varies with the change in moisture content.…”
Section: Modern Wusn Technologies and Advancement Of Acousticsmentioning
confidence: 99%